2009
DOI: 10.1161/circresaha.109.197996
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycogen Synthase Kinase-3β in Cardioprotection

Abstract: Abstract-Limitation of infarct size by ischemic/pharmacological pre-and postconditioning involves activation of a complex set of cell-signaling pathways. Multiple lines of evidence implicate the mitochondrial permeability transition pore (mPTP) as a key end effector of ischemic/pharmacological pre-and postconditioning. Increasing the ROS threshold for mPTP induction enhances the resistance of cardiomyocytes to oxidant stress and results in infarct size reduction. Here, we survey and synthesize the present know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
273
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(288 citation statements)
references
References 144 publications
(203 reference statements)
11
273
1
3
Order By: Relevance
“…GSK‐3β is known to phosphorylate and inhibit antiapoptotic proteins p‐Bcl‐2 (ser70) and p‐mcl‐1 (ser159) 15, 16. Mcl‐1 localizes to the mitochondria, where it interacts with and antagonizes proapoptotic Bcl‐2 family members and inhibits apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…GSK‐3β is known to phosphorylate and inhibit antiapoptotic proteins p‐Bcl‐2 (ser70) and p‐mcl‐1 (ser159) 15, 16. Mcl‐1 localizes to the mitochondria, where it interacts with and antagonizes proapoptotic Bcl‐2 family members and inhibits apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This key regulator of the heat shock response has been shown to be inactivated by GSK-3β by specific phosphorylation, rendering the transcription of cytoprotective genes inactive. GSK-3β itself is regulated through a phosphorylation step at the serine-9 residue by different upstream kinases (Juhaszova et al 2009). This regulation of GSK-3β is influenced by cell stressors such as hypoxia, oxidative stress, heat shock, but also by factors such as changes in glucose concentration and high GDP content.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work by our group (Juhaszova et al, 2004;Juhaszova et al, 2009) as well as by others (Garlid et al, 2003;Halestrap, 1989;Sato et al, 1998) the following reveal key manifestations of mKATP activation in cardiomyocytes in response to KCOs: (1) flavoprotein (FP) oxidation, (2) modulation of mitochondrial regulatory swelling (i.e., due to mitochondrial K + accumulation), (3) volume activation of respiration (as a consequence of #2), (4) inhibition of GSK-3β activity via ser-9 phosphorylation, and (5) increased mPTP reactive All rights reserved. No reuse allowed without permission.…”
Section: Potassiummentioning
confidence: 99%
“…The mPTP is a key end-effector of protection signaling: the threshold for mPTP-induction by ROS being significantly reduced after ischemia-reperfusion injury and contributing to cell death, but beneficially increased by preconditioning, postconditioning and other forms of protection signaling, contributing to cell survival (Juhaszova et al, 2004;Juhaszova et al, 2009). We showed that cell protection involves convergence of a multiplicity of potential and distinct upstream pathways (including opening of mKATP), each acting via inhibition of GSK-3β on the end effector, the mPTP complex, to limit its induction (see Figure 4H-K).…”
Section: Effects On Mptp Ros-thresholdmentioning
confidence: 99%